Boosting the efficiency and the stability of low cost perovskite solar cells by using CuPc nanorods as hole transport material and carbon as counter electrode. (February 2016) - Zhang, Fuguo; Yang, Xichuan; Cheng, Ming; Wang, Weihan; Sun, Licheng
Abstract: Low temperature printable carbon cathode based perovskite solar cell was for the first time interfacial engineered with dopant free, nanorod-liked copper phthalocyanine (CuPc) to facilitate charge transportation. Both the CuPc and low temperature processed carbon are potentially noble metal-free and highly stable. By incorporating CuPc nanorods as hole-selective contact material, together with the printable low temperature processed carbon as cathode material, considerably high power conversion efficiency (PCE) of 16.1% was successfully obtained, which is comparable to or even a little higher than the device with state-of-the-art doped spiro-OMeTAD as HTM and noble metal Au as back electrode. Moreover, dramatically enhanced durability relative to doped-spiro-OMeTAD/Au based device was demonstrated by this newly developed device. Detailed excellent capability in accelerating charge extraction and suppressing charge recombination can be disclosed with steady state and time-resolved photoluminescence analysis and electrochemical impedance spectroscopy. To the best our knowledge, this is the highest efficiency that has been reported for PSCs based carbon counter electrode. The work presented here demonstrates an important step forwards to practical applications for PSCs, as it paves the way for developments of cost-effective, stable but still highly efficient PSCs, and offers the promise for a low-cost, mass-manufacturable technology that is compatible with current large-scale printing infrastructure. Graphical abstract: Highlights: Cost-effective, noble metal-free, stable and highly efficient perovskite solar cells were demonstrated. Low temperature (100 °C) processed carbon counter electrode based perovskite solar cells was for the first time interfacial engineered with copper phathalocyanine nanorods. Copper phathalocyanine with distinctive morphology of nanorods were found to be efficient in charge extraction and charge recombination suppression. The best cell afforded impressive PCE of 16.1% being one of the highest efficiency for carbon counter electrode based perovskite solar cells among reported results.